Intercultural communication a contextual approach - Neuliep, James W. (Houghton Mifflin Co., 2000)
[The book] is designed for college students taking their first course in intercultural communication. The purpose of the book is to introduce students to some of the fundamental topics, theories, concepts, and themes that are the center of the study of international communication. [The book] alerts the student to the importance and necessity of intercultural communication as we enter the dawn of the twenty-first century. [It] defines culture as an accumulated pattern of values, beliefs, and behaviors, shared by an identifiable group of people with a common history and verbal and nonverbal code system. [Then it] focuses on the microcultural context [and] environmental context ... examines the perceptual contexts of the interactions ... discusses the sociorelational context [and] the development of intercultural relationships.... Virtually all of the chapters in this book contain cultural conversations. -Pref.